Islam without Domination: NU Women and Moderate Ethics at the Grassroots Level in Urban Muslim Society in Depok, Indonesia - Rofiah, Nur; Abdillah, Akhmad Mughzi; Nursyabani, Mirza; Wirdah, Nailul (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2025)
Nahdlatul Ulama (NU) women in Depok develop ethical resistance to the dominance of conservative Islamic politics, which is controlled by a certain political party. This study aims to examine how NU women articulate and engage in ethical resistance through organizational involvement, and how these actions advance religious moderation and the concept of the maṣlaḥah family in an urban Islamic context. Using an interdisciplinary framework that integrates social capital theory, counterpublics, and ethical agency, the research examines the symbolic, structural, and practical strategies employed by NU women across Muslimat NU, Fatayat NU, and IPPNU. The results reveal that NU women create a distinct social environment founded on justice, compassion, and inclusiveness. Their activism offers a counterbalance to conservative narratives in Depok and helps to revive Islamic traditions in modern and contextual ways. By contesting exclusivity in urban culture and opening up space for a more compassionate, inclusive, and transformative expression of Islam, this grassroots movement contributes to broader social change.